Diseño, construcción e implementación de un sistema de monitoreo y control para un cuarto de crecimiento en la industria alimenticia (2021)
The present work (TIG), Design, construction and implementation of a monitoring and control system for a growth room. It is designed to improve the process in the food industry specifically in the bakery sector, making use of current technology.